Focus Group Discussion (FGD) to Improve Employment Competency Learning Activities and Outcomes Students at SMP N 7 Purworejo - Widiyati, Widiyati (Indonesian Journal of History Education, 2022)
This study aims to determine the increase in learning activities of Class VIII-B students of 7th Junior High School in Purworejo after following the Social Studies Learning Process with a Focus Group Discussion (FGD) Model and to determine the increase in social learning outcomes of the subject matter of employment after following the Social Studies learning process. This research was conducted using a classroom action research model. The Classroom Action Research (CAR) was conducted at the 7th Junior High School in Purworejo. The subjects in this study were students of class VIII-B, which amounted (to 30 students consisting of 12 men and 18 women). The selection of class VIII-B as a research subject is due to the activity; the activeness of students during the teaching and learning process is very low and can even be said to be passive; in line with that, the learning outcomes of students are also meager compared to other classes so it is necessary to increase student learning activities. This study's results indicate a significant increase in the two cycles carried out in activities and learning outcomes.